2018
DOI: 10.1111/jfb.13783
|View full text |Cite
|
Sign up to set email alerts
|

Food searching behaviour in adult Atlantic codGadus morhuaduring acoustic training: social learning and leadership within a school

Abstract: Food searching behaviour in a group of individually tagged 1-5 kg Atlantic cod Gadus morhua was studied in a set of three experiments in a sea cage with two underwater platforms, where restricted amounts of food was delivered several times per day during an acoustic training period. It took c. 1 week to train 20 naïve cod to associate low frequency (250 Hz) sound with food, whereas the training time was reduced to less than 2 days when 19 naïve G. morhua were accompanied with one trained fish. The fish formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Due to this spatial arrangement, leading individuals often have greater access to encountered resources (7) and can make decisions that benefit themselves at a cost to their followers (8). Followers, however, can benefit from being led by more informed individuals without having to privately sample or detect information in the environment that can be costly to acquire (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this spatial arrangement, leading individuals often have greater access to encountered resources (7) and can make decisions that benefit themselves at a cost to their followers (8). Followers, however, can benefit from being led by more informed individuals without having to privately sample or detect information in the environment that can be costly to acquire (9,10).…”
mentioning
confidence: 99%
“…For example, although there are observational studies finding that individuals at the front of groups are disproportionally attacked (17,18), individuals in these groups determined their own positions through self-organization, and leadership and followership covaried with other individual attributes. As the tendency to lead is often associated with goal orientation driven by greater information (19) or greater need (10), individuals that are less risk averse [i.e., bold (20)], less sociable (21), hungrier (22), or larger (7) are more likely to occupy positions at the front of the group. These individual traits can result in an increased risk of predation even when individuals are alone, and leading others can be cognitively demanding (23), which may further increase risk for leaders through reduced vigilance for predators.…”
mentioning
confidence: 99%
“…Species‐level responses may also be explained by behavioural attributes, such as hunting tactics or ability to capture and consume prey. G. morhua is an opportunistic predator (Kullander et al ., 2012), actively searching for prey and occasionally undertaking feeding migrations (Björnsson et al ., 2018). It is also a facultative schooler, meaning that it can forage alone or form large shoals (Björnsson et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with the “20/80 rule” and the so‐called “small world” network topology where a few long‐distant edges in the network can increase transmission of information and disease (Watts & Strogatz, 1998 ). From a management perspective, superfeeders may be the key to removal strategies, since they are contributing more to social learning via their network position and possibly encouraging other fish to feed at baited sites (e.g., “leaders” in cod aquaculture (Björnsson et al, 2018 )). Indeed, superfeeders in this study were, on average, detected earlier at baiting sites in both 2019 and 2020 seasons (Figure S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In many fishes, length is an indicator of social hierarchy, age, and possibly also temperament (Froese & Pauly, 2021 ; Huntingford et al, 2010 ; Ward et al, 2006 ) where the largest tend to dominate. Björnsson et al ( 2018 ) hypothesized that the largest fish might be present at the bait most often and consume most of it due to their higher caloric requirements and higher energy costs associated with active foraging. Our observations are in line with other studies that have found that body size could predict variation in contact behavior; for example, in a study of the contact behavior of deer mice ( Peromyscus maniculatu)s , larger mice were more connected and had more contacts than smaller mice (Clay et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%